RANCANG BANGUN SISTEM INFORMASI e-Commerce PADA TOKO AMPEK PANGERAN PALEMBANG - Tata Sutabri; Naufal Rahmatullah Ramadhan (Jurnal Salome : Multidisipliner Keilmuan, 2023)
Currently information technology is experiencing very rapid development, along with human needs which also continue to grow. Technology plays a very important role in human life. At present, those who are not accustomed to keeping up with technological developments, it is certain that they will become backward people. The sales system used at Toko Ampek Pangeran Palembang currently still uses social media and telephone facilities because it does not yet have E-Commerce. In recording sales transaction data, Toko Ampek Pangeran Palembang still uses a manual system, namely recording using Microsoft Excel. So that errors and delays often occur in making sales reports. The solution proposed to overcome the problem of Toko Ampek Pangeran Palembang to develop its sales business is by using E-Commerce. E-Commerce is a medium of trade transactions between sellers and buyers using internet media. The advantage gained through E-Commerce is that it can improve the services of the Toko Ampek Pangeran Palembang because by using online sales, promotions regarding new products are easier to display, transactions become easier and also reduce operational costs such as paper and catalog printing.